PENGGUNAAN SMART BOOK UNTUK SISWA KESULITAN MEMBACA DI SMA UTAMA WIDYALAYA ASTIKAN DHARMA - I Wayan Numertayasa; Ni Made Kembar Rianti (Universitas Negeri Makassar, 2025)
The purpose of this research was to examine the effectiveness of using a Smart Book as an alternative learning medium to assist students with reading difficulties at SMA Utama Widyalaya Astika Dharma. This study employed a qualitative method with data collected through observation and interviews. The findings revealed that the Smart Book improved students’ reading skills gradually through interactive features such as images, audio, and engaging quizzes. Moreover, the media enhanced students’ motivation and active participation during learning activities. However, some challenges were identified in navigation and user instructions, which need further improvement. Overall, the use of Smart Bookproved to be effective and suitable as an instructional medium for students with reading difficulties at the senior high school level.